The fat mass, estimated glomerular filtration rate, and chronic inflammation in type 2 diabetic patients - Šálek, Tomáš; Adamíková, Alena; Ponížil, Petr (Journal of clinical laboratory analysis, 2020)
BACKGROUND: The aim of the study was to analyze the degree of obesity and its associations with age, gender, inflammation, an estimated glomerular filtration rate (eGFR), and liver function in type 2 diabetes mellitus (T2DM) patients. METHODS: A total of 874 consecutive adult Caucasian T2DM patients from outpatient diabetic clinic were included in the study. The relative fat mass (RFM) and body mass index (BMI) were used as obesity markers. Serum creatinine and cystatin C were used for the GFR estimation. Serum high-sensitive C-reactive protein (hsCRP) was used as the indicator of inflammation. RESULTS: The median, interquartile range (IQR) of RFM in females was higher than that in males (44.8 (42.3-47.2) % vs 31.3 (28.8-34.1) %, respectively; P < .0001). The median (IQR) of BMI in females was no higher than that in males (30 (27-34) kg/m2 vs 30 (27-34), respectively; P = .5152). The obesity prevalence was 99% in males and 98% in females according to RFM. BMI recognized obesity in 51% males and 53% females. RFM was positively associated with hsCRP in both males (rs  = .296, P < .0001) and females (rs  = .445, P < .0001). ALT was positively correlated with eGFRcys in both males (rs  = .379, P < .0001) and females (rs  = .308, P < .0001). CONCLUSION: The RFM equation leads to higher obesity prevalence compared to BMI. Women have higher RFM compared to men. The kidney function was positively correlated with ALT serum concentrations.
Keywords: tuková tkáň; Diabetes Mellitus, Type 2; chronická renální insuficience; Liver Function Tests; senioři; index tělesné hmotnosti; Aged; Male; diabetes mellitus 2. typu; lidé; Retrospective Studies; lidé středního věku; Humans; Body Mass Index; retrospektivní studie; Middle Aged; C-Reactive Protein; zánět; hodnoty glomerulární filtrace; průřezové studie; mužské pohlaví; C-reaktivní protein; Cross-Sectional Studies; ženské pohlaví; Adipose Tissue; Inflammation; Female; Renal Insufficiency, Chronic; jaterní testy; Glomerular Filtration Rate